Could e-commerce activities drive to climate change mitigation? Novel evidence from panel quantile regression model - Doran, Nicoleta Mihaela; Manta, Alina Georgiana; Badareu, Gabriela; Berceanu, Dorel; Doran, Marius Dalian; Manta, Florin Liviu (Journal of Business Economics and Management, 2025)
This study aims at shedding light on how e-commerce contributes to climate change in European Union countries. To explore this relationship, we introduced a novel index designed to measure the evolution of climate change as the dependent variable, while considering e-commerce activities as the independent variable within 2011 to 2022 period. Our investigation of the correlation between these variables employed a panel quantile regression model. The outcomes revealed a statistically significant increasing trend for higher quantiles. This finding indicates that, as we traverse the climate change index from lower to higher percentiles, the impact of e-commerce becomes more conspicuous and is statistically significant. This underscores that the influence of e-commerce on climate change intensifies as we move towards the upper percentiles of the climate change index. To address how e-commerce affects climate change, it becomes imperative to introduce and enforce the concept of environmental responsibility in the management of e-commerce activities. This could involve adopting sustainable practices, optimizing packaging materials, and encouraging eco-friendly delivery methods. Policymakers and businesses alike should consider these findings in their efforts to strike an equilibrium between the convenience of e-commerce and the need to curb its environmental impact.